Comparison of Three retrieval accuracy of image retrieval technology - He Bai Qing; Wang Zi Min (MATEC Web of Conferences, 2016)
With the development of society, it began between the various sectors and industries increasingly high integration of information, and the image retrieval technology has played an increasingly important role in the current exchange of information. Image retrieval faster, higher accuracy, then the computer used in image retrieval technology is more advanced. By now several popular image retrieval technology introduction, pointed out that the principles of these types of image retrieval technology and difficulties, comparative study of the advantages and disadvantages of these three image retrieval technology, so that we can retrieve the image retrieval accuracy further understanding.